Acceptability of Suubi+Adherence intervention to improve ART adherence in Southern Uganda: A qualitative analysis - Josephine Nabayinda; Ozge Sensoy Bahar; Phionah Namatovu; Proscovia Nabunya; Samuel Kizito; Anita Kabarambi; April Thames; Fred M. Ssewamala (PLoS ONE, 2026)
In Uganda, 150,000 young people were living with HIV by the end of 2023. While Antiretroviral therapy (ART) is effective in reducing HIV transmission, youth in SSA, including in Uganda, face greater challenges with ART adherence compared to adults. Poverty-focused interventions have been recommended to improve adherence and viral load suppression. In this manuscript from Suubi+Adherence-Round 2 study, we explored the acceptability of Suubi+Adherence, a combination intervention aimed at improving ART adherence among adolescents living with HIV in Uganda that was tested in a six-year longitudinal study called Suubi+Adherence (2012–2018). We conducted semi-structured in-depth interviews with 36 youths who participated in the Suubi+Adherence intervention, which comprised matched savings accounts, mentorship, financial management, and business development training. Interviews explored participants’ motivations for joining, their experiences with the intervention, and the facilitators and barriers to intervention attendance. Informed by the Theoretical Framework of Acceptability, data were analyzed using thematic analysis and Dedoose software. Our results showed that the primary motivation for participation was the opportunity to learn about savings and income-generating activities. Participants also appreciated the Wisepill -an Electronic Monitoring Device, which reminded them to take their medication. Key facilitators for intervention attendance included transport reimbursements, family support, and content relevance. Challenges included long travel distances and associated costs, session timing conflicts with household responsibilities, and other personal obligations. Despite these challenges, participants highlighted the practical relevance of the intervention content, which aligned with their real-life experiences and needs. Our findings offer valuable insights into the acceptability of a combination intervention aimed at improving ART adherence among youth. These results have important implications for HIV treatment programs and policy in Uganda, particularly given the country’s high HIV prevalence. The parent randomized clinical trial is registered in the clinical trials database (NCT03307226).